The Effect of Education, Economic Growth, Labor and City Minimum Wages on Poverty in the Ex-Residency of Surakarta in 2017-2021: Pengaruh Pendidikan, Pertumbuhan Ekonomi, Tenaga Kerja dan Upah Minimum Kabupaten Kota Terhadap Kemiskinan di Eks-Karesidenan Surakarta Tahun 2017-2021 - AZIZAH, SALWA NUR; Setyowati, Eni (Procedia of Social Sciences and Humanities, 2022)
his study aims to analyze how much influence Education, Economic Growth, Labor, District/City Minimum Wages have on Poverty in Surakarta Residency in 2017-2021. Poverty as a related variable, while education, economic growth, labor and district/city minimum wages are independent variables. The analytical technique used is panel data regression analysis using the Eviews 10 program computer. This study uses secondary data obtained from the Central Statistics Agency for a period of 5 years starting from 2017-2021. This research is expected to be a material consideration for policy making for local governments in the formulation of a policy to reduce poverty.